الاسطورة في الانثروبولوجيا البنيوية عند كلود ليفي ستروس - زروقي فتيحة; اشراف: ارفيس علي (جامعة محمد بوضياف المسيلة, 2025)
لقد نظر كلود ليفي ستروس للأسطورة من منظور أنثربولوجي بنيوي، حيث تعرض لبنية ووظيفة الأسطورة، ورأى أن الأساطير تتألف من وحدات سردية (ميثيمات) تفهم ضمن علاقات تقابلية، وتكمن وظيفتها في حل التناقضات الفكرية داخل المجتمعات. وقد بحث كلود ليفي ستروس في الأسطورة بين العلم والفن، موضحا أن الأسطورة بنية عقلية شبيهة باللغة تقع بين التفسير العلمي للواقع والتعبير الجمالي عنه. وهذا مما يجعلها جسرا بين الفكر العقلاني والحدسي، وبالتالي فالأسطورة وفقا لكلود ليفي ستروس تفهم من خلال بنيتها لا مضمونها وأن دراستها تكشف عن البنية العميقة للفكر الإنساني. الكلمات المفتاحية:الأسطورة، الأنثربولوجيا، البنيوية، العلم، الفن ، اللغة Abstract: Claude Lévi-Strauss viewed myth from a structural anthropological perspective, examining the structure and function of myth. He argued that myths consist of narrative units (themes) that are understood within contrastive relationships, and that their function lies in resolving intellectual contradictions within societies. He explored myth between science and art, explaining that myth is a mental structure similar to language, situated between the scientific interpretation of reality and its aesthetic expression. This makes it a bridge between rational and intuitive thought. According to Lévi-Strauss, myth is understood through its structure, not its content, and its study reveals the deep structure of human thought. Keywords: myth, anthropology, structuralism, science, art, language